An electrochemical biosensor for rapid detection of E. coli O157:H7 with highly efficient bi-functional glucose oxidase-polydopamine nanocomposites and Prussian blue modified screen-printed interdigitated electrodes. Issue 18 (30th June 2016) - Xu, Meng; Wang, Ronghui; Li, Yanbin
Abstract : An electrochemical biosensor was developed based on the bifunctional ABs/GOxext /AuNPs/MBs-GOx@PDA magnetic PMNCs that can rapidly and sensitively detect E. coli O157:H7. Abstract : The presence of pathogenic bacteria in foods has always been a great threat to the wellbeing of people and the revenue of food manufacturers. Therefore, the demand for advanced detection methods that can sensitively and rapidly detect these pathogens has been of great importance. This study reports an electrochemical biosensor for rapid detection of E. coli O157:H7 with the integration of bifunctional glucose oxidase (GOx)–polydopamine (PDA) based polymeric nanocomposites (PMNCs) and Prussian blue (PB) modified screen-printed interdigitated microelectrodes (SP-IDMEs). The core–shell magnetic beads (MBs)–GOx@PDA PMNCs were first synthesized by the self-polymerization of dopamine (DA). Gold nanoparticles (AuNPs) were dispersed on the surface of PMNCs through biochemical synthesis to achieve further highly efficient adsorption of antibodies (ABs) and GOx. The final product ABs/GOxext /AuNPs/MBs–GOx@PDA PMNCs served as the carrier to separate target bacteria from food matrices as well as the amplifier for electrochemical measurement. The unbound PMNCs were separated by a filtration step and transferred into glucose solution to allow the enzymatic reaction to occur. The change of the current response was measured with an electrochemical detector using PB-modified SP-IDMEs. The constructed biosensor has been proven to be able to detect E. coli O157:H7 with the detection limit of 10 2 cfu ml −1 . The bifunctional PMNCs contain a high load of enzyme and can optimally utilize the binding sites on bacterial cells, which efficiently amplify the signals for measurement. The biosensor in this study exhibited good specificity, reproducibility, and stability and is expected to have a great impact on applications in the detection of foodborne pathogens.